2002
DOI: 10.1159/000057606
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Pentosidine Levels Measured by a Newly Developed Method Using ELISA in Patients with Chronic Renal Failure

Abstract: The plasma pentosidine levels in patients with renal disease were measured by a simple method which was established for plasma and urinary pentosidine determinations. The method, which can be completed within a few hours, involves pretreating plasma with proteolytic enzyme (pronase) and measuring the concentration of pentosidine in the sample by ELISA using antipentosidine antibodies. The prepared antibodies showed no cross-reaction with the raw materials for pentosidine synthesis or with compounds having simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
46
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 20 publications
4
46
0
1
Order By: Relevance
“…Takeuchi et al reported that blood CML levels were not associated with HbA 1c in patients with type 2 diabetes [15], while Sanaka et al found that blood pentosidine and blood glucose levels were not correlated [8]. These reports are consistent with our findings, suggesting that the production of CML or pentosidine does not directly reflect the severity of hyperglycemia.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Takeuchi et al reported that blood CML levels were not associated with HbA 1c in patients with type 2 diabetes [15], while Sanaka et al found that blood pentosidine and blood glucose levels were not correlated [8]. These reports are consistent with our findings, suggesting that the production of CML or pentosidine does not directly reflect the severity of hyperglycemia.…”
Section: Discussionsupporting
confidence: 90%
“…A significant increase of CML and pentosidine was only noted after the onset of CRF along with the elevation of serum creatinine. Since CML and pentosidine are eliminated by renal excretion, their blood levels are directly proportional to the creatinine level and are inversely proportional to creatinine clearance [7,8]. Therefore, the present results reflected the fact that the blood levels of CML and pentosidine are influenced by renal clearance.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…This method involved pretreating sera with a proteolytic enzyme (pronase) and then measuring concentrations of pentosidine in the sample by ELISA [13].…”
Section: Measurement Of Pentosidinementioning
confidence: 99%
“…HC (nmol/mL) was examined by HPLC (39) and pentosidine (μg/mL) was assayed by ELISA as previously described (40). The concentration of MMP-9 to vascular damage by activating MMP-9 (42), and both HC and pentosidine were in general increased with inflammation monitored by hsCRP, both oxidative markers were neither correlated with each other, nor serum levels of hsCRP and MMP-9 in WS.…”
Section: Measurementsmentioning
confidence: 99%